2000
DOI: 10.1038/77811
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 induction of IgE: dependence on CD4+ T cells, IL-4 and STAT6

Abstract: Overproduction of immunoglobulin E (IgE) and T helper cell type 2 (TH2) cytokines, including interleukin 4 (IL-4), IL-5 and IL-13, can result in allergic disorders. Although it is known that IL-4 is critical to the polarization of naïve CD4+ T cells to a TH2 phenotype, both in vitro and in many in vivo systems, other factors that regulate in vivo IL-4 production and TH2 commitment are poorly understood. IL-18, an IL-1-like cytokine that requires cleavage with caspase-1 to become active, was found to increase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
280
1
5

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(298 citation statements)
references
References 34 publications
12
280
1
5
Order By: Relevance
“…However, our results indicate that this is unlikely, because the absence of IL-12 did not decrease either IL-13 production by MLN cells or IL-13-dependent worm expulsion. Previous studies also suggested that IL-18 could induce IL-4 and associated IgE and IgG1 production in vivo [19,20]. In the IL-4-dominant response to T. muris, IL-18 has further been shown to down-regulate IL-13 production [13].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, our results indicate that this is unlikely, because the absence of IL-12 did not decrease either IL-13 production by MLN cells or IL-13-dependent worm expulsion. Previous studies also suggested that IL-18 could induce IL-4 and associated IgE and IgG1 production in vivo [19,20]. In the IL-4-dominant response to T. muris, IL-18 has further been shown to down-regulate IL-13 production [13].…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, when IL-18 was combined with IL-2, there was a synergistic induction of IL-13 in both T and NK cells [17]. IL-18 can also induce IgE, IgG1 and Th2 cytokine production in murine experimental models [19,20], and IL-18 transgenic mice produce higher levels of IL-4, IL-5, IL-13 and IFN-c [21]. Taken together these studies indicate that IL-18 is a pleiotropic cytokine that may under some circumstances augment type 2 as well as type 1 immunity.…”
Section: Introductionmentioning
confidence: 99%
“…While IL-18 clearly enhances Th1 responses, it is less clear whether IL-18 is capable of initiating Th1 differentiation in the absence of IL-12 6 7 8 9 10. Although a majority of published reports link IL-18 with Th1-associated functions, IL-18 has recently been shown to augment Th2 responses 11 12 13 14. Administration of IL-18 to mice led to an increase in IL-4 production and elevated serum IgE.…”
Section: Introductionmentioning
confidence: 99%
“…IL-18, in turn, helps induce the IL-12 high affinity receptor, establishing a feed-forward Th1-amplifying loop [11,17]. Surprisingly, in the absence of a Th1-polarizing environment, IL-18 can promote the differentiation of Th2 cells, a CD4 + T cell subset dominating allergic responses and characterized by the expression of IL-4 and IL-13 [11, 17,18].…”
Section: Main Effects Of Il-1b and Il-18 On T Helper Cell Polarizationmentioning
confidence: 99%